1970
DOI: 10.1104/pp.45.6.703
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Photorespiration in Typha latifolia

Abstract: NaH'4CO3 (105 Cpm) to 1.3 ml of the enzyme preparation. At intervals, 0.4-ml samples were removed and acidified with 0.1 ml of 6 N acetic acid. Controls consisted of a zero time sample that was acidified immediately upon mixing the reaction components, and a reaction mixture lacking ribulose-1, 5-diP which was acidified at the end of the experimental period. The same enzyme preparation procedure was used for phosphopyruvate carboxylase except that dithioerythritol was sometimes substituted for reduced glutathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1970
1970
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Scirpus lacustris, Cyperus papyrus, Allium cepa) have shown that little (i.e. 0.25-2.2%) of the CO 2 in the aerenchyma is recycled and used for photosynthesis (McNaughton and Fullem, 1970;Singer et al, 1994;Byrd et al, 1995). The isotopic signature of leaf d 13 C at the SJFM confirmed that CO 2 recycling does not play a major role in increasing GPP.…”
mentioning
confidence: 82%
“…Scirpus lacustris, Cyperus papyrus, Allium cepa) have shown that little (i.e. 0.25-2.2%) of the CO 2 in the aerenchyma is recycled and used for photosynthesis (McNaughton and Fullem, 1970;Singer et al, 1994;Byrd et al, 1995). The isotopic signature of leaf d 13 C at the SJFM confirmed that CO 2 recycling does not play a major role in increasing GPP.…”
mentioning
confidence: 82%
“…Panicum milioMes possesses a higher PEP carboxylase activity than C3 species [21]. In Typha latifolia, McNaughton and Fullem reported that malate was not a photosynthetic product but might be derived from glycolate metabolism [16]. Our own results suggest that PEP carboxylase may be involved in CO2 fixation by sunflower leaves.…”
Section: Photosynthetic Characteristics O/isolated Cellsmentioning
confidence: 49%
“…Nitrate reductase (EC (1.6.6.4) was assayed using the in vivo method of Klepper et al (1971). Glycolate oxidase (EC 1.1.3.1) was assayed according to McNaughton and Fullen (1970).…”
Section: Enzyme Assaymentioning
confidence: 99%